Impact of bounding attachments on breastfeeding success in primipara postpartum mothers - Safaah, Nurus; Yunitasari, Esti; Prasetyo, Budi; Triharini, Mira; Feriani, Pipit (International Journal of Public Health Science (IJPHS), 2024)
Breastfeeding is more than just generating healthy breast milk. It is a cooperative activity involving both parties. This study examined how ligature ties affect primiparous women's ability to nurse their babies after giving birth. This type of research is cross-sectional. The study sample consisted of 144 primiparous postpartum women whose children were aged between 0 and three months. The entire sample employed in this study consisted of 106 primiparous postpartum women, selected by a combination of simple random sampling and probability. Questionnaires were used to collect data on attachment factors and breastfeeding success. A correlation value of r=0.437 was obtained, indicating a very positive association between the two variables, and the results demonstrated a significance level of ≤0.05. This correlation implies that effective nursing is mostly dependent on the mother and infant developing strong emotional attachment. These results further emphasize the importance of providing primiparous postpartum mothers with sufficient assistance and direction to enhance their bonding and breastfeeding experiences. Teaching caregivers and medical professionals the value of emotional connection and how it affects nursing outcomes are also essential. Given the established link between effective nursing and emotional attachment, healthcare providers can provide customized interventions and support to improve mother-child bonds throughout the postpartum phase.